Exploratory Study of Autoantibody Profiling in Drug‐Induced Liver Injury with an Autoimmune Phenotype - Lammert, Craig; Zhu, Chengsong; Lian, Yun; Raman, Indu; Eckert, George; Li, Quan‐Zhen; Chalasani, Naga (Hepatology communications, 2020)
Drug‐induced liver injury (DILI) sometimes presents with an autoimmune hepatitis‐like phenotype (AI‐DILI), and it is challenging to distinguish it from de novo autoimmune hepatitis (AIH). We conducted a study to identify autoantibodies unique to AI‐DILI by profiling serum autoantibodies. Autoantibodies were quantified using an autoantigen array containing 94 autoantigens from four groups: AI‐DILI (n = 65), DILI controls (n = 67), de novo AIH (n = 17), and healthy controls (HCs; n = 30). In 37 patients with AI‐DILI, samples were also collected 6 months after presentation. AI‐DILI and de novo AIH had similar anti‐neutrophil antibody and anti‐smooth muscle antibody prevalence. Compared to HCs, de novo AIH had an increase in many immunoglobulin G (IgG; 35 [46.1%]) and IgM (51 [70%]) autoantibodies, whereas AI‐DILI had an increase of IgM (40 [54.8%]) but not IgG autoantibodies. DILI controls had a similar IgG and IgM profile compared to HCs. Comparing de novo AIH to AI‐DILI identified 18 (23.7%) elevated IgG but only one (1.4%) IgM autoantibodies, indicating the unique IgG autoantibody profile in de novo AIH. Compared to DILI and HCs, increased IgM autoantibodies in AI‐DILI and de novo AIH were common; however, AI‐DILI induced by different drugs showed different frequencies of IgM autoantibodies, with nitrofurantoin‐related AI‐DILI showing a higher number of increased IgM autoantibodies. AI‐DILI autoantibody levels at diagnosis and at 6 months showed a significant decline in 37 IgM autoantibodies. A model with highly correlated IgG and IgM was fitted into multivariate logistic regression and revealed an area under the curve of 0.87 (95% confidence interval, 0.79‐0.95) to distinguish de novo AIH from AI‐DILI. Conclusion: The unique IgG and IgM autoantibody signature appears to be a promising biomarker for distinguishing AI‐DILI from de novo AIH.